Скифское поселение на Немировском городище: общие данные о памятнике - Смирнова, Г.И. (Материалы по археологии, истории и этнографии Таврии, 1998)
The materials on Nemirov hill-fort in the region of the Southern Bug (the work on them the author has started to work out) are given in this article. One can find the answers to the questions concerning the degree of study of inner fortification during the whole period of excavation in Nemirov (1909-1910, 1946-1948). Roundshaped pit-dwellings and some other objects are described here for the first time. Much attention is given to the rich collection from Nemirov, impressive and peculiar due to Hallshtat appearance. Ceramic material is classified; a small group of crockery characteristic for late-Chernoles culture is singled out. The author has all the reasons'to date pre-Scythian and Scythian settlements in the hill-fort back to the 8th - 6th centuries B.C. Having studied the information about the three graves in the hill- fort (the graves were found by S.S.Gamchenko), the author disagrees with M.I.Artamonov and doubts about their relating to the Scythian period.